The Impact Of The Social Inclusion Awareness Module On The Attitude And Knowledge Of Students In Nigeria - Ipadeola, Mairo Hamid (2019)
People with disabilities (PWD) throughout history have been subjected to a multiplicity of oppressive social attitude which include neglect, rejection, hostility, bullying, distrust, pity and over-protection among others (WHO, 2011) while lack of knowledge informed these attitudes. The study set out to study the impact of the Social Inclusion Awareness Module (SIAM) on the attitude and knowledge of students in Nigeria. The SIAM was developed using ADDIE instructional design. A sequential mixed method design was applied in this study. The qualitative approach used phenomenological research design, with a face to face interview involving fourteen (14) students with disabilities and eleven (11) regular students purposefully selected from one institution in Nigeria. The qualitative data were analysed by thematic analysis and the findings revealed that Student with disabilities (SWD) expressed reduced social inclusion in terms of social participation, economic access, physical/environmental access and supportive /valued social relationships, this was due to lack of public enlightenment and inavailability of facilities to reduce the impact of disability. SWDs proposed education for the public (society) and provision of equipment / facilities as solution to social inclusion. The quantitative approach used a single group method of quasi experimental design involving pre-test, intervention and post-test. Questionnaire was used for the pre-test and post-test, eight (8) weeks intervention of SIAM module was taught through lecture method to 491 student’s The data was analysed using descriptive statistics and paired t-test.